Meal-related difficulties and weight loss in older people: Longitudinal data from MAPT study. Issue 11 (November 2020) - Soriano, Gaëlle; De Souto Barreto, Philippe; Virecoulon Giudici, Kelly; Cantet, Christelle; Guyonnet, Sophie; Vellas, Bruno; Rolland, Yves; Andrieu, Sandrine; ,; Vellas, Bruno; Guyonnet, Sophie; Carrié, Isabelle; et al.
Summary: Background: Difficulties with meal-related activities (preparing meals and food shopping) may influence food intake, and contribute to nutritional risk among elderly people. All known studies on this topic had a cross-sectional design, thereby no causal relationships could be derived. We aim to investigate if difficulties with meal-related activities can contribute to subsequent weight loss in community-dwelling older people. Methods: We used data of older subjects from the MAPT Study (n = 1531, median age = 74 years, 64% women), who provided prospective data on weight every 6 months and cognitive, physical condition, and functional capacities every year during a 3-year period. Difficulties preparing meals and shopping were evaluated each year with the Alzheimer's Disease Cooperative Study-Activities of Daily Living Prevention Instrument (ADCS ADL-PI) Scale. The risk of losing weight (≥5% or ≥ 3 kg in the following year) was estimated using a time-dependent Cox regression model. Results: During the 3-year follow-up, a total of 851 subjects experienced at least a 5% or 3 kg weight loss. Two hundred thirty-seven subjects declared having difficulties with meal preparation at least once, and 133 declared having difficulties shopping. Subjects reporting any meal-related difficulties were older (p < 0.001), had more depressive symptoms (p < 0.001), and a lower physical function (p < 0.001) compared to those without difficulties. They also had a lower cognitive score (preparing meals: p < 0.001; shopping: p = 0.005) and a lower body mass index (preparing meals: p = 0.005; shopping: p = 0.023) at the end of the study. Meal-related activities were not associated with weight loss in unadjusted analysis and after adjustment for sex, age, depression, physical and cognitive status. Conclusion: Difficulties preparing meals and shopping had no effect on weight loss in community-dwelling older people, despite their association with advanced age, functional decline, and depressive symptoms.